GROWTH, YIELD AND WATER USE OF MAIZE AS INFLUENCED BY DRIP IRRIGATION SCHEDULES AND NITROGEN LEVELS - Y. DEEPTHI KIRAN*, V. SUMATHI and G. PRABHAKARA REDDY, (The Journal of Research ANGRAU, 2019)
The field experiment was conducted for two consecutive years (2013-14 and 2014-15) to evaluate theyield and economic returns from maize under different irrigation schedules and nitrogen levels. The experimentwas laid out in split-plot design and replicated thrice by applying four irrigation schedules under the mainplotand three nitrogen levels under subplot. The growth parameters and yield of maize were found superior withweekly check basin irrigation, however, were on par with drip irrigation at 0.9 IW/CPE ratio. Among the nitrogenlevels tried, 240 kg N ha-1 recorded higher growth and yield. The interaction between the irrigation schedulesand nitrogen levels indicated the better growth parameters and higher yield with irrigation scheduled either byweekly check basin method or through drip irrigation at 0.9 IW/CPE ratio along with 240 kg N ha-1. The wateruse efficiency was also higher with drip irrigation scheduled at 0.9 IW/CPE ratio. The results revealed thatmaize crop can be grown economically with the irrigations scheduledat 0.9 IW/CPE ratio through drip irrigationalong with 240 kg N ha-1.